Optical Coherence Tomography Angiography in Extensive Macular Atrophy with Pseudodrusen-Like Appearance - Rajabian, Firuzeh (Transl Vis Sci Technol, 2020)
PURPOSE: Analyses of quantitative features of optical coherence tomography angiography (OCTA) in patients affected by extensive macular atrophy with pseudodrusen-like appearance (EMAP). METHODS: In a prospective case-control study, patients and age- and gender-matched healthy controls underwent complete ophthalmologic examination, including best corrected visual acuity (BCVA) measurement, biomicroscopy, fundus autofluorescence and spectral-domain optical coherence tomography (Spectralis HRA; Heidelberg Engineering GmbH, Heidelberg, Germany), and OCTA scans (DRI OCT Triton; Topcon Corporation, Tokyo, Japan). Vessel density in the superficial capillary plexus and deep capillary plexus (DCP) in the retina and choriocapillaris (CC) in the macula and optic disc were measured. The one-way analysis of variance test with Bonferroni correction was used for statistical assessments. RESULTS: Seven patients (14 eyes) and 10 controls were included in the study. The mean follow-up period was 3 ± 0.8 years. The mean BCVA of patients at baseline was 0.81 ± 0.43 (logarithm of the minimum angle of resolution [LogMAR]) and 1.05 ± 0.38 (LogMAR) at the final follow-up visit (P = 0.006). Quantitative analyses of retinal vessels revealed significant alterations, especially in the DCP and CC, in both atrophic and junctional zones in retina of EMAP patients compared with preserved zones and controls. CONCLUSIONS: OCTA analysis characterized three different retinal regions in EMAP disease, corresponding to progressively deeper perfusion defects. Further investigations are warranted to explore the correlation between DCP changes and the extension of atrophy. TRANSLATIONAL RELEVANCE: By expanding our pilot study, we may better define EMAP on the basis of vascular changes and eventually recognize earlier the direction of enlargement of atrophy by means of OCTA analyses.